Conditional Selection of B Cells in Mice With an Inducible B Cell Development - Hobeika, Elias; Dautzenberg, Marcel; Levit-Zerdoun, Ella; Pelanda, Roberta; Reth, Michael (Frontiers in Immunology, 2018)
Developing B cells undergo defined maturation steps in the bone marrow and in the spleen. The timing and the factors that control these differentiation steps are not fully understood. By targeting the B cell-restricted mb-1 locus to generate an mb-1 allele that expresses a tamoxifen inducible Cre and another allele in which mb-1 expression can be controlled by Cre, we have established a mouse model with an inducible B cell compartment. With these mice, we studied in detail the kinetics of B cell development and the consequence of BCR activation at a defined B cell maturation stage. Contrary to expectations, transitional 1-B cells exposed to anti-IgM reagents in vivo did not die but instead developed into transitional 2 (T2)-B cells with upregulated Bcl-2 expression. We show, however, that these T2-B cells had an increased dependency on the B cell survival factor B cell activating factor when compared to non-stimulated B cells. Overall, our findings indicate that the inducible mb-1 mouse strain represents a useful model, which allows studying the signals that control the selection of B cells in greater detail.